Cons and pros: prison education through the eyes of the prison educated*. Issue 1 (2nd January 2019) - Ahmed, Reaz; Johnson, Michael; Caudill, Craig; Diedrich, Nicholas; Mains, David; Key, Adam
ABSTRACT: While much has been written within academic journals about prisoners, rarely is there anything written by prisoners. In this essay, we, a group of prisoners who are earning or have earned college degrees while incarcerated in Texas, address the purpose, merits, and pitfalls of prison education and reform. Written as a response to the essays appearing in this special issue, we discuss our experiences of being othered as inmates, the impact of societal bias against us, our perspectives on prison education, and our own ideas for reforming prisons and making them more humane.